Enhanced, tailored antenatal care to reduce anaemia in pregnancy - Comprehensive Anaemia Programme and Personalized Therapies (CAPPT) trial. - Kharel, Chandani. (Tufts University. Tisch Library., 2020)
This poster discusses the trailored antenatal care to reduce anemia in pregnancy.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy